Seeing beyond 2020: an economic evaluation of contemporary and emerging strategies for elimination of Trypanosoma brucei gambiense - C Simone Sutherland, PhD; Christopher M Stone, PhD; Peter Steinmann, PhD; Marcel Tanner, PhD; DrPhD Fabrizio Tediosi, PhD (Elsevier, 2017)
Summary: Background: Trypanosoma brucei (T b) gambiense is targeted to reach elimination as a public health problem by 2020 and full elimination by 2030. To achieve these goals, stakeholders need to consider strategies to accelerate elimination. Hence, we aimed to model several options related to current and emerging methods for case detection, treatment, and vector control across settings to assess cost-effectiveness and the probability of elimination. Methods: Five intervention strategies were modelled over 30 years for low, moderate, and high transmission settings. Model parameters related to costs, efficacy, and transmission were based on available evidence and parameter estimation. Outcomes included disability-adjusted life-years (DALYs), costs, and long-term prevalence. Sensitivity analyses were done to calculate the uncertainty of the results. Findings: To reach elimination targets for 2020 across all settings, approaches combining case detection, treatment, and vector control would be most effective. Elimination in high and moderate transmission areas was probable and cost-effective when strategies included vector control and novel methods, with incremental cost-effectiveness ratios (ICERs) ranging from US$400 to $1500 per DALY averted. In low transmission areas, approaches including the newest interventions alone or in combination with tiny targets (vector control) were cost-effective, with ICERs of $200 or $1800 per DALY averted, respectively, but only strategies including vector control were likely to lead to elimination. Results of sensitivity analyses showed that allowing for biennial surveillance, reducing vector control maintenance costs, or variations of active surveillance coverage could also be cost-effective options for elimination, depending on the setting. Interpretation: Although various strategies might lead to elimination of T b gambiense, cost-effective approaches will include adoption of emerging technologies and, in some settings, increased surveillance or implementation of vector control. Funding: Bill & Melinda Gates Foundation.